PENGARUH PENERAPAN MODEL PEMBELAJARAN OPEN ENDED TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DENGAN VARIABEL MODERATOR MOTIVASI BELAJAR - Sri Mulyati; Yeyen Suryani; Iyan Setiawan (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
Abstract: The problem in this study is the low ability of students's critical thinking, seen from apreliminary study which shows that the majority of students get grades below the minimalcompleteness criteria. This research is a quasi-experimental design with a Two-factor betweensubjectdesign. The subjects of the study were the social studies class X students of Cikijing SeniorHigh School 1 2018-2019 school year. Where class X IPS 1 as a control class and class X IPS 3as an experimental class where the total students of the two classes are 66 students. The results ofthis study are to show that: (1) there are differences in critical thinking skills between studentswho are taught with the open ended learning model compared to the lecture method. (2) there aredifferences in critical thinking skills between students who have high learning motivation andstudents who have low learning motivation. (3) there is no interaction between open endedlearning models with student motivation to influence students's critical thinking skills.Kata kunci : Model Pembelajaran Open Ended, Kemampuan Berpikir Kritis, dan MotivasiBelajar.